The influence of advertising appeals on consumer perceptions of athlete endorser brand image. Issue 3 (27th May 2019) - Kunkel, Thilo; Walker, Matthew; Hodge, Courtney M.
ABSTRACT: Research question: Analogous to traditional brands, athlete (i.e. personal) brands require management and maintenance. While the use of athlete endorsers is an effective marketing strategy for companies wanting to increase visibility, research has failed to indicate how advertising influences perceptions of the athlete endorser (i.e. spill-over effects). This research addresses this gap by examining the influence of four advertising appeals on perceptions of an athlete endorser expertise, trustworthiness, attractiveness and likeability. Research method: Experimental between-subjects study design. MANOVAs with post hoc analyses were used to examine differences between advertisement appeals. Regression was used to examine the influence of respondent attitudes towards the advertisement on perceptions of the athlete endorser. Results: Results revealed that perceptions of the athlete endorser were influenced by the type of advertising appeal. In opposition to existing research, emotional appeals did not outperform informational appeals. However, results demonstrated that spill-over effects existed from the advertisement appeal to the athlete endorser. Implications: The results indicate that advertising influences consumer perceptions of athlete endorsers. Consequently, athletes must consider how advertising appeals are applied and consider the residual effects that are generated from product advertisements.